Trichoscopic findings in various alopecias at tertiary referral center: A cross-sectional study - Mamatha P; V Neha; Shishira R Jartarkar; Shalini Sampath; Rakesh R Madireddy (Wolters Kluwer Medknow Publications, 2022)
Background: Hair disorders are a common complaint that baffles dermatologists due to multiple causes. Trichoscopy is a noninvasive technique used to diagnose and monitor the progression of various hair disorders. Purpose: To observe the trichoscopic patterns of various hair disorders to assist with differentiation. Methods: This was a cross-sectional observational study done in 256 patients with alopecia. After a detailed history, clinical examination, and relevant investigations, trichoscopy was performed using a Dermlite (3Gen LLC, Sanjuan Capistrano, CA, USA) dermoscope. Results: Out of 256 patients, 154 were male and 102 were female. Most of the cases were in the age group of 21-40 years (66.4%). Nonscarring alopecias (93.35%) were common compared to scarring alopecias (5.8%). The most common alopecia noted in our study was Androgenetic alopecia 125 patients (48.82%), followed by telogen effluvium 48 patients (19.1%), the common trichoscopic follicular features noted were short vellus hair 161 (62.8%), yellow dots (61%), hair diameter variation 125 (48.82%), and black dots (21.87%). The commo interfollicular features are seen were arborizing vessels 109 (42.6%) and pigmentation in 12 patients (4.68%). Significant findings observed in each group were hair diameter diversity in androgenetic alopecia, exclamatory mark in Alopecia Areata, comma hair in tinea capitis. Cicatricial alopecias are characterized by loss of follicular ostia along with inflammatory signs such as perifollicular scales and casts. Conclusion: Trichoscopy is a very valuable and useful tool to diagnose various hair disorders by understanding the various trichoscopic patterns specific for each disease.